What has given rise to the interest in mixed methods research today? - Creswell, John W. ([Thousand Oaks, Calif. : SAGE], 2010)
The speaker takes as his starting point the idea that this methodology is fairly new, about 20 years old. It is now often described as the third methodoligical movement - an amalgam of quantitative and qualitative research.
"SAGE research methods online."
Title from home page (viewed Jan. 26, 2011).
Online video.
Includes transcript.
Specialized.
Mode of access: World Wide Web.
Keywords: elektronické knihy; electronic books; Mixed methods research